The Magical Statuette of Yuya with Excursus of Spell 151 of the Book of the Dead at the Egyptian Museum Cairo (CG 51035, SR 4/151) - Ouda, Ahmed M. Mekawy (The journal of Egyptian archaeology, 2025)
This paper publishes the magical statuette of the ‘God’s Father’ Yuya, which is in the Cairo Museum (CG 51035). The statuette was found in Yuya’s tomb (KV46). All of Yuya’s other funerary statuettes are classified as shabtis (CG51024–34, MMA30.8.56–58) and bear chapter six of the Book of the Dead, with the exception of the uninscribed CG 51036. Statuette CG 51035 was looted during the turmoil of the Egyptian Revolution in 2011 and recovered in 2014; other shabtis were also looted (CG 51029) or retrieved (CG 51024–26, 51031, 51034, 51036) after they had been stolen. The state of preservation of this magical statuette has not been examined since the discovery of KV46 in 1905. This paper explores the crucial inscription on the statuette, containing sections of chapter 151 (F, D) of the Book of the Dead. It also gives a full description, transcription, transliteration, translation, and comment on this statuette.